A multilevel model of life satisfaction among old people: individual characteristics and neighborhood physical disorder - Camila Teixeira Vaz; Amanda Cristina de Souza Andrade; Fernando Augusto Proietti; César Coelho Xavier; Amélia Augusta de Lima Friche; Waleska Teixeira Caiaffa (BMC, 2019)
Abstract Background Considering the lack of studies that examine built environmental factors associated with life satisfaction among old people in developing countries, particularly those focused on Brazil, the aim of this study was to estimate the prevalence of life satisfaction among old adults residents in a Brazilian urban center and to investigate its association with individual characteristics and objective measures of the built environment. Methods A household survey (N = 832) in Belo Horizonte, Minas Gerais, Brazil (2008-2009) and a Systematic Social Observation (SSO) was used in this study. Life satisfaction was assessed through Self-Anchoring Ladder Scale, developed by Cantril, in 1965. Participants' answers were categorized as satisfied (rungs 6-10) and dissatisfied (rungs 0-5). A Multilevel Poisson regression analysis with robust variance was performed. Results The prevalence of satisfaction with life was approximately 82%. Higher prevalence of life satisfaction was significantly associated with old people who reported higher incomes, higher religious participation, who practice physical activity and who perceive their health as good and very good. In contextual level, results showed that when the contextual features were adjusted separately by the individual characteristics they were no longer significant. The results also showed a lower prevalence of life satisfaction among those living in neighborhoods with higher physical disorder, even after adjusting for individual and other contextual characteristics. Conclusions The present findings suggest that life satisfaction should be assessed whenever evaluating urban redevelopment programs designed to improve neighborhood characteristics, reducing physical disorder, especially among old adults.